Corporate Culture and Internal Communication Influence on Millenial Employee Engagement - Mohammad Reza Prasetya; Dorien Kartikawangi (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2021)
Employee engagement is a complex concept that includes employee’s commitment, satisfaction, loyalty, and extra efforts in carrying out roles in daily life at work. Building employee engagement is not easy. The company is facing a shifting generation to millennials with unique characteristics. This was becoming a challenge yet an opportunity for the company. This study aimed to describe the influence of corporate culture and internal communication on employee engagement of millennial employees. This study used quantitative methods with millennial employees as the respondent and used multiple linear regression analysis techniques. The results of this study indicated that company culture has a positive and significant effect on millennial employee engagement. Then, internal communication has a positive and significant effect on millennial employee engagement. Finally, corporate culture and internal communication have a positive and significant influence on millennial employee engagement.